Micro-teaching and its role in teacher preparation programs (Journal of the College of Basic Education, 2022)
One of the things that have been of great importance in educational systems is preparing student teachers and preparing them for the requirements of the teaching profession that contribute to building the personality of the individual and producing the human resource necessary to build a prosperous society. There is no doubt that the profession of this profession cannot be immediate teaching, but requires preparation, attention and training, as it is based on scientific foundations of specialized knowledge, specific teaching skills, and technical practices, including mini-teaching, which represents the main pillar in the programs for preparing students (teachers) with what they perform Of an important role in raising their teaching efficiency and improving their performance. Therefore, the current research aims to present a theoretical framework for micro-teaching and its role in teacher preparation programs. The researcher reached several conclusions, including: -The micro-teaching is effective in student teacher acquisition of basic teaching skills.Micro-teaching makes student teachers have an appropriate and acceptable amount of direction towards the teaching profession.Mini-teaching provides an opportunity for teacher students to self-evaluate and enable them to adjust their teaching performance on a go.